RESILIENCE AND SATISFACTION OF ONLINE BUYING BEHAVIOUR IN TIRUCHIRAPPALLI CITY MUNICIPAL CORPORATION - Muthuvel, P.; Jerome, V. Bastin (International Journal of Psychosocial Rehabilitation, 2020)
The present study is entitled as “Resilience and Satisfaction of Online Buying Behaviour in Tiruchirappalli city Municipal Corporation”. This paper focuses on the resilience and satisfaction of online buying behaviour. It is the process of overcoming the negative effects of risk exposure, coping successfully with traumatic experiences, and avoiding the negative trajectories associated with risks. The basic element for resilience is that there should be risk and protective factors available which can get an optimistic result or can decrease negative result. The theory of resilience basically focuses on youth‟s exposure to risk on the strength instead of weakness and also on understanding healthy growth even with the presence of risk. Resilience is defined as a class of phenomena characterized by patterns of positive adaptation in the context of significant adversity or risk. The outcomes of the present research help the online shoppers for the adoption of better resilience and improve their online buying behaviour. The research was a survey type, which consists of random sampling of 384 people in Tiruchirappalli district. The investigator has constructed and validated the Resilience and Satisfaction of Online Buying Behaviour Scale by self under the guidance of his research guide. Personal data sheet was prepared by the investigator. The interpretation of data was done with statistical methods in percentage analysis, mean, standard deviation and „t‟- test.